2020
DOI: 10.1111/ijcp.13589
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic and bleeding outcomes in patients with atrial fibrillation and valvular heart disease: A descriptive nationwide cohort study

Abstract: Aims The risks of thromboembolism and bleeding in patients with atrial fibrillation (AF) and valvular heart disease (VHD) are sparsely described. We described the risk of events in non‐anticoagulated and anticoagulated patients with AF and VHD according to the evaluated heart valves, rheumatic or artificial valve classification (EHRA classification), EHRA Type 1 and Type 2 VHD, and within subgroups of EHRA Type 1 and Type 2 VHD. Methods and Results Cohort study of AF patients with coexisting VHD, identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
4
5
0
Order By: Relevance
“…However, in the literature there is no comparison between patients with EHRA type 2 and those with non-valvular AF regarding this score. The high anticoagulation rate in group 1 of this study is also similar to the recent published study, in which the rates were 62.5% for patients with moderate to severe mitral stenosis and 100% for those with mechanical replacement of the prosthetic valve [18]. On the other hand, the anticoagulation rate in group 2 was lower than in the aforementioned study, which showed rates between 50.8% and 67.1% for patients in the EHRA type 2 categorization.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in the literature there is no comparison between patients with EHRA type 2 and those with non-valvular AF regarding this score. The high anticoagulation rate in group 1 of this study is also similar to the recent published study, in which the rates were 62.5% for patients with moderate to severe mitral stenosis and 100% for those with mechanical replacement of the prosthetic valve [18]. On the other hand, the anticoagulation rate in group 2 was lower than in the aforementioned study, which showed rates between 50.8% and 67.1% for patients in the EHRA type 2 categorization.…”
Section: Discussionsupporting
confidence: 88%
“…Nationwide cohort study with a large sample of patients with valvular heart disease and AF, but with 90% of patients with EHRA type 2, demonstrated a rate of 14.6% and 18.6% of thromboembolism in patients with EHRA type 1 and EHRA type 2, respectively [17]. A study from the same group showed that the rate of previous thromboembolism ranged from 10.0% to 14.6% between patients in both groups [18]. The higher rate of thromboembolism in our study can be explained by the higher proportion of patients with moderate to severe mitral stenosis in group 1, which was 89.5%, compared to the rate of 29.2% in the study mentioned above.…”
Section: Discussionmentioning
confidence: 95%
“…Only a few post hoc sub‐analyses of the existing randomized, controlled trials have examined patients with both AF and VHD, and the proportion of patients with aortic stenosis was underrepresented (6%–12%), 12 , 19 , 20 , 21 despite aortic stenosis being one of the most prevalent VHDs in recent patients with AF and VHD (17%–62% with aortic stenosis). 2 , 22 , 23 , 24 Consequently, the effectiveness and safety of NOAC versus warfarin in AF patients with aortic stenosis has not been specifically investigated, although guidelines currently allow for use of NOACs in AF patients with aortic stenosis (and without a mechanical heart valve or concomitant moderate/severe mitral stenosis). 25 , 26 …”
mentioning
confidence: 99%
“… 1 It is an independent cause of mortality and morbidity associated with thromboembolic and bleeding events, irrespective of underlying cardiac rhythm. 4 , 5 AF patients have historically been dichotomized as “valvular” AF or “nonvalvular” AF. However, clinical definitions of these terms have been conflicting, causing confusion among researchers and practitioners.…”
Section: Introductionmentioning
confidence: 99%